A priori probabilities in Y23 mixture analysis: Non-contributor experiments using simulated powerplex® Y23 Y-STR mixtures. (December 2017) - Moore, D.; Clayton, T.; Thomson, J.
Abstract: When Y-STRs are used in the investigation of sexual offences, it is not uncommon to observe mixed profiles from two or more male individuals. If the haplotype of a person of interest is fully represented in the mixed profile then clearly that male could not be excluded as a possible contributor to that mixture. The evaluation of the weight-of-evidence in such cases is more complex than in autosomal STRs (where the loci are inherited independently). Methods for calculating a likelihood ratio for a Y-STR mixture have been published (Wolf et al.[1] ). However, these methods require complex mathematics to perform. To further our understanding of the significance of a match within a Y-STR mixture we have devised a non-contributor experiment on simulated mixtures derived from published PowerPlex® Y23 haplotypes from 19, 630 different men[2] to estimate the average probability of a random inclusion (P i ).